2002
DOI: 10.1029/2001gl014368
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of boundary layer ozone transport and photochemical production in east Asia in the wintertime

Abstract: The transport and chemical transformation of boundary layer ozone in east Asia in January 1997 was investigated using the Models‐3 Community Multiscale Air Quality (CMAQ) modeling system with meteorological fields calculated by the Regional Atmospheric Modeling System (RAMS). The predicted ozone concentrations were compared with ground‐level observations at four remote sites in Japan and it was found that the model reproduces many of the important features in the observations. Examination of several high ozone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 11 publications
2
31
0
Order By: Relevance
“…It has successfully applied to investigate the Asian continental outflow of carbon monoxide, ozone, and aerosol sulfate to the western Pacific Ocean by a number of serious researches (Zhang et al, 2002;Uno et al, 2005;Yamaji et al, 2006).…”
Section: Model Description and Validationmentioning
confidence: 99%
“…It has successfully applied to investigate the Asian continental outflow of carbon monoxide, ozone, and aerosol sulfate to the western Pacific Ocean by a number of serious researches (Zhang et al, 2002;Uno et al, 2005;Yamaji et al, 2006).…”
Section: Model Description and Validationmentioning
confidence: 99%
“…In this paper, the air quality modeling system Regional Atmospheric Modeling System-Community Multi-scale Air Quality (RAMS-CMAQ) 21 was employed to study the complex sequence of physical and chemical processes involved in acid deposition in East Asia. The RAMS-CMAQ modeling system contains two major components, the Community Multi-scale Air Quality (CMAQ) 22 and the Regional Atmospheric Modeling System (RAMS).…”
Section: Model Descriptionmentioning
confidence: 99%
“…They also provide recent emission trends, but such a long-term CTM study has not yet been reported for Asia. As successful applications for Asian air quality studies, the community multi-scale air quality model (CMAQ; Byun and Ching, 1999) has been used intensively by Zhang et al (2002), Uno et al (2005), Tanimoto et al (2005), and Yamaji et al (2006a). Herein, we report the results of systematic analyses of seasonal and interannual variations of NO 2 VCDs based on GOME data and the regional scale CTM, CMAQ, and sensitivity experiments with the latest emission inventory in Asia from 1996 to 2003.…”
Section: Introductionmentioning
confidence: 99%